Chromebook digital media innovation on Tana Tidung folklore material to improve reading literacy of fifth grade students - Misrianah Misrianah; Juharyanto Juharyanto; Ade Eka Anggraini (Journal of Research in Instructional, 2026)
This study investigates the effectiveness of Chromebook-based digital media in improving elementary students’ reading literacy and learning motivation in learning Tana Tidung folklore. A mixed-methods approach was employed, combining a quantitative pretest–posttest design with qualitative data from observations, interviews, and questionnaires. Results from the paired sample t-test showed a significant increase in reading literacy (p < 0.001; Cohen’s dz = 4.70), indicating a very large effect. Thematic analysis further revealed that multimedia features helped students comprehend narrative structures and identify moral and cultural values more clearly. Students demonstrated higher intrinsic motivation, active participation in digital discussions, and increased independence in accessing learning materials. Teachers also reported enhanced classroom engagement, although challenges such as limited device availability and unstable internet occasionally hindered learning activities. Overall, the findings show that Chromebook-based digital media effectively supports literacy development, motivation, and cultural understanding, highlighting its potential as a meaningful digital learning innovation for elementary education.